Treatment of environmental pollution of industrial water contaminated with sulfates in the Dora refinery (Journal of the College of Basic Education, 2022)
Purpose of this research was the examination of the environmental situation of industrial wastewater of Al- Dora -Refinery . Also the effect of chemical precipitation method applied to treat polluted wastewater was investigated . Al-Dora Refinery consumes big amounts of water for different purposes . This water is heavily polluted during its passage through the refinery and cause great damage to the environment unless the water is treated to remove pollution . This research was carried out in three main stages. The first stage included the examination of polluted water passing through five main stations of the refinery and going to the treatment unit by measuring some essential physical and chemical properties, like water temp. ,electrical conductivity ,turbidity, PH-Value , total dissolved solids T.D.S , suspended solids ,sulphate ion ,phosphate ion , biological oxygen demand (BOD) , chemical oxygen demand (COD), phenol and oils .The second stage included measuring of the above menthioned physical and chemical properties between the treatment unit ( P10) and outgoing water of ( P18) during the period from November 2014 until September 2015.The third stage included the treatment of sulfate -polluted water using calcium hydroxide .The results of the research showed very good efficiency of water treatment with calcium hydroxide reducing sulfate concentration under the internationally allowed limit of 400 ppm.